1995
DOI: 10.1002/1097-0142(19950501)75:9<2251::aid-cncr2820750910>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of anti-GD3 ganglioside monoclonal antibody R24 and recombinant human macrophage-colony stimulating factor in patients with metastatic melanoma

Abstract: Background. Macrophages activated by macrophage‐colony stimulating factor (M‐CSF) are potent immune effector cells and can mediate both in vitro cytotoxicity and antitumor effects in vivo. A Phase I trial combining M‐CSF with R24, a mouse monoclonal antibody against GD3 ganglioside that has been shown to localize to melanoma tumors, induce inflammation at tumor sites, and result in major tumor responses in some patients with melanoma was performed. Methods. Nineteen patients with metastatic melanoma received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Seminal trials in melanoma using R24 (GD3‐specific IgG3 antibody) demonstrated a major tumor regression in patients with advanced disease . Most common toxicities of GD3 antibody include pruritus and urticaria . The high prevalence of GD3 expression in sarcomas and DSRCT shown in this study should provide a rationale for future antibody strategies directed at these tumors.…”
Section: Discussionmentioning
confidence: 63%
“…Seminal trials in melanoma using R24 (GD3‐specific IgG3 antibody) demonstrated a major tumor regression in patients with advanced disease . Most common toxicities of GD3 antibody include pruritus and urticaria . The high prevalence of GD3 expression in sarcomas and DSRCT shown in this study should provide a rationale for future antibody strategies directed at these tumors.…”
Section: Discussionmentioning
confidence: 63%
“…A murine mAb (R24) recognizing GD3 has been tested in patients in various clinical trials. Regression of melanoma metastasis after treatment has been documented repeatedly (22)(23)(24)(25)(26). More recently, a chimeric antibody KM871 showed its efficacy in the treatment of melanomas in a nude mice model by slowing the tumor growth (27).…”
mentioning
confidence: 99%
“…Thrombocytopenia has been associated with the administration of a number of cytokines, including GM-CSF (Nash et al, 1995), M-CSF (Koike et al, 1986;Sanda et al, 1992;Minasian et al, 1995), G-CSF (Lindemann et al, 1989), IL-2 (Paciucci et al, 1990), stem cell factor (SCF) (Schuening et al, 1993) and Flt3 ligand (unpublished observations). There may be a common mechanism responsible for cytokine-related decreases in platelet counts.…”
Section: Discussionmentioning
confidence: 99%